The Effect of Exercise and Balance on the Accuracy of the Service Corner in the Takraw Game on Tondano 3 High School Students - Lanongbuka, Alen Inlans; Lomboan, Ellen (Universitas Negeri Manado, 2024)
This research uses a quantitative approach with an experimental method. This study aims to determine the ability of the service corner between plyometric training and weight training, find out the interaction between training and balance of the ability of the service corner, know the ability of the service corner between plyometric training and weight training for those who have high balance and know the ability of the service corner between plyometric training and weight training for those who have low balance in students of SMA Negeri 3 Tondano. In this study, the instrument was used as a data collection tool, namely the accuracy of the service corner test. To test the research hypothesis two-way ANAVA analysis was used as a factorial design with a significance level of ÃŽÂ± = 0.05 which was then followed by the Tukey test to find out which groups were superior. The results showed no difference in the effect of plyometric training and weight training. There is no interaction between training and balance of corner service abilities in the soccer takraw game. For groups of students who have high balance it is better to use weight training compared to plyometric training to improve corner service abilities. For groups of students who have a low balance, it is better to use plyometric training than weight training to improve corner service ability.